Metabolizable energy and nutrient digestibility of detoxified castor meal and castor cake for poultry - João Batista Matos Júnior; Adélio Nunes Dias; Camila Ferreira Delfim Bueno; Priscila Avelino Rodrigues; Álvaro Luís Carvalho Veloso; Daniel Emygdio de Faria Filho (Revista Brasileira de Zootecnia, 2011)
This experiment aimed to determine the metabolizable energy and the digestibility of detoxified castor meal and castor cake nutrients for broilers. A total of 180 Cobb-500TM broilers from 21 to 32 days of age was randomly distributed in three treatments with six replicates of 10 broilers - 5 males and 5 females. The experimental treatments were a reference-diet and two test-diets composed of 80% of reference-diet and 20% of detoxified castor cake or castor meal. The adaptation period ranged from 21 to 27 days of age and the total excreta collection period ranged from 28 to 32 days of age. The detoxified castor meal presented apparent metabolizable energy of 2,032 kcal/kg of natural matter, apparent metabolizable energy corrected for nitrogen balance of 1,829 kcal/kg of natural matter and the digestibility coefficients of 57.8% dry matter, 68.4% crude protein, 10.5% crude fiber, 35.9% nitrogen free extract, 80.0% ether extract and 26.6% ash. In the detoxified castor cake, the apparent metabolizable energy content was 2,550 kcal/kg of natural matter, the nitrogen corrected apparent metabolizable energy balance was of 2,320 kcal/kg of natural matter and the digestibility coefficients of 60.6% for dry matter, 77.2% for crude protein, 14.0% for crude fiber, 45.7% for nitrogen free extract, 85.4% for ether extract and 28.2% for ash. The metabolizable energy and digestibility of nutrients in detoxified castor cake are higher than in the detoxified castor meal.